Pembuatan Teknologi Tepat Guna Alat Pembakaran Sampah Untuk Mencegah Pencemaran di Kelurahan Untia - Mashudi Gani; Deselfia DNM Sahari; St. Syahriati; Andi Herlina; Darwis Darwis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Waste is one form of problem that everyone often encounters in their environment. Waste is the waste of products or goods that have been used by their users, so that the remaining results are discarded and do not function again. The purpose of this service is to provide material on making appropriate technology for waste incineration tools to prevent pollution in the untia village. The method of application in this activity is the counseling method through demonstration and also the lecture and discussion method at community meetings in untia village. The results of community service activities regarding the manufacture of appropriate technology for waste incineration tools to prevent pollution in untia village have been carried out well and received a positive response from the untia village community.